Coping Motives as a Mediator of the Relationship between Trauma Exposure and Substance Misuse in South African Adolescents - Assim, Ayesha (Department of Psychology, 2023)
South African adolescents experience high rates of trauma exposure in their homes and communities, which places them at a greater risk of developing substance misuse. Studies in high-income countries have shown that substance misuse in traumatised adults is driven by their ‘coping motives': maladaptive beliefs that substances help cope with negative affect. However, very few studies to date have explored this risk pathway in trauma-exposed adolescents, particularly in lower resource contexts. The current study examined whether coping motives mediate the relationship between different forms of trauma exposure (child maltreatment versus community violence) and different forms of problems related to substance use (alcohol and marijuana) in a sample of South African adolescents. High school learners at three government schools in Cape Town (N = 688; M age = 15.03) completed self-report measures of child maltreatment and community-based trauma exposure, alcohol and marijuana use, alcohol and marijuana-related problems, and motives for using alcohol and marijuana. Child maltreatment and community violence exposure both predicted alcohol-related problems while child maltreatment, but not community violence exposure, predicted marijuana-related problems. Coping motives, and to a lesser extent conformity motives, partially mediated the relationship between child maltreatment and alcohol-related problems, while coping motives but no other motives partially mediated the relationship between child maltreatment and marijuana-related problems. The relationship between community violence exposure and alcohol-related problems was not mediated by any alcohol use motives. The findings suggest that coping motives increase the risk that adolescents who experience child maltreatment will have substance use problems. Targeting coping motives could be an important focus for substance misuse interventions for trauma-exposed South African adolescents.